(3dGejI GdYQH (B- (3bUjOIs - (3GHf GdhQOj , YeQ Hf eXaQ Hf YeQ Hf eMeO GHf CHj GdahGQS GdeYQj GdcfOj, Rjf GdOjf CHh MaU,J (B749 (3g` s ((3YHOGdUeO s)
(3ChdgG (B:s
(3CbjehG Hfj oCej oUOhQ eWjoce aEfj Edi bhe ShGce dCejd hGdCYbd GdPj bO JYJUe HGdLHd jbGd hYd CYbd, hCQhjI oYbdGA s
(3BNQgG (B:s
(3hGdCYbd GdPj bO JYJUe HGdLHd jbGd hYd CYbd, hCQhjI oYbdGA s
(3GfXQ GdLRA GdChd GdCQbGe (B693-694 (3COHs
(3hGdbSe GdQGHY Qbe (B889 (3COHs
(3HChdgG hba eDQN SfI (B1236(3g`s
(3ajgG TQM HYV GdCHjGJs
(3hGdTQM Hbde fSNj MSfs
(3cJHgG fbdkG Yf NW jGbhJ GdeSJYUej GdNWGW YHOGdUeOs
Keywords: (3GdCOHs